2017
DOI: 10.1016/j.midw.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Chronological narratives from smoking initiation through to pregnancy of Indigenous Australian women: A qualitative study

Abstract: Aboriginal women report multiple influences in the progression of early smoking to pregnancy and beyond. Potential opportunities to intervene include: a) childhood, coming of age, pregnancy, post-natal, in-between births; b) key influencers; c) environments, and d) targeting concurrent substance use. Morning sickness appears to be a natural deterrent to continued smoking. Depression, and its relationship to smoking and quitting in Australian Indigenous pregnant women, requires further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 34 publications
(39 reference statements)
0
45
0
Order By: Relevance
“…32,37 Women who have smoked during pregnancy have reported that coming of age as a smoker, being able to purchase one's own supplies legally, and exposure to alcohol accelerated tobacco dependence. 36 Concurrent alcohol use and smoking initiation as well as earlier uptake of smoking are independent predictors of reduced intentions to stop smoking in Australian Indigenous men and women of reproductive age. 38 High tar and nicotine brands were marketed to Indigenous populations using Aboriginal images as recently as 1998.…”
Section: Prevalence Of and Factors Predisposing To Tobacco Use Among mentioning
confidence: 97%
See 4 more Smart Citations
“…32,37 Women who have smoked during pregnancy have reported that coming of age as a smoker, being able to purchase one's own supplies legally, and exposure to alcohol accelerated tobacco dependence. 36 Concurrent alcohol use and smoking initiation as well as earlier uptake of smoking are independent predictors of reduced intentions to stop smoking in Australian Indigenous men and women of reproductive age. 38 High tar and nicotine brands were marketed to Indigenous populations using Aboriginal images as recently as 1998.…”
Section: Prevalence Of and Factors Predisposing To Tobacco Use Among mentioning
confidence: 97%
“…Mothers are particularly influential for young women. [32][33][34][35][36] Adolescent Indigenous girls may be more influenced by social networks and peer pressure than are boys. 32,37 Women who have smoked during pregnancy have reported that coming of age as a smoker, being able to purchase one's own supplies legally, and exposure to alcohol accelerated tobacco dependence.…”
Section: Prevalence Of and Factors Predisposing To Tobacco Use Among mentioning
confidence: 99%
See 3 more Smart Citations